The Effect of Liquidity Level and Loan Installment Loans on Profitability in Go Public Banking Companies in Indonesia - Agus Setyo Utomo; Retnoning Ambarwati (International Journal of Seocology, 2022)
This study aims to analyze the Effect of Liquidity Levels and Installment Loans on Profitability of Go Public Banking Companies in Indonesia during the Covid-19 pandemic. This research is a causative research with a population of banking companies that go public in the country. While the sample of this study was determined by the purposive sampling method, and processed as many as 84 samples from 42 banking companies in the observation period (2020-2021). The type of data used is secondary data obtained from financial statements published by banking companies at www.idx.co.id. The analytical method used is multiple regression analysis. The results of the study show that the level of liquidity partially affects the profitability of banking companies that go public in Indonesia, the loan installment allowance partially affects the profitability of banking companies that go public in Indonesia and the level of liquidity and installment allowances simultaneously affects the profitability of banking companies that go public. in Indonesia.